2017
DOI: 10.1007/s13365-017-0512-5
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine dependence does not contribute substantially to white matter abnormalities in HIV infection

Abstract: This study investigated the association of HIV infection and cocaine dependence with cerebral white matter integrity using diffusion tensor imaging (DTI). 135 participants stratified by HIV and cocaine status (26 HIV+/COC+, 37 HIV+/COC−, 37 HIV−/COC+, and 35 HIV−/COC−) completed a comprehensive substance abuse assessment, neuropsychological testing, and MRI with DTI. Among HIV+ participants, all were receiving HIV care and 46% had an AIDS diagnosis. All COC+ participants were current users and met criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
(100 reference statements)
1
7
0
Order By: Relevance
“…Moreover, greater anterior than posterior WMH burden is consistent with evidence that HIV is associated with frontostriatal compromise . Yet, DTI and morphometric studies commonly reveal widespread effects of HIV throughout the brain . Interestingly, it has been suggested that WMH may represent a more advanced form of white matter pathology than the subtler, more extensive forms detected by DTI .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, greater anterior than posterior WMH burden is consistent with evidence that HIV is associated with frontostriatal compromise . Yet, DTI and morphometric studies commonly reveal widespread effects of HIV throughout the brain . Interestingly, it has been suggested that WMH may represent a more advanced form of white matter pathology than the subtler, more extensive forms detected by DTI .…”
Section: Discussionsupporting
confidence: 60%
“…31,32 Yet, DTI and morphometric studies commonly reveal widespread effects of HIV throughout the brain. [31][32][33][34][35][36][37][38] Interestingly, it has been suggested that WMH may represent a more advanced form of white matter pathology than the subtler, more extensive forms detected by DTI. 10,39 Future studies are needed to further clarify the clinical relevance of regional white matter lesions in HIV+ samples, as well as to examine the relation of WMH burden to DTI findings.…”
Section: Discussionmentioning
confidence: 99%
“…Those widespread differences in diffusion metrics persist in our cohort despite cocaine abstinence could suggest that HIV is the primary driving factor of the neuropathology. Indeed, this idea is supported by results from a recent study showing no effect of current cocaine use on WM pathology in HIV+ subjects ( 20 ). However, it should be noted that Cordero et al’s recent findings differ from many those of studies demonstrating WM impairment in current cocaine dependence in the absence of HIV ( 15 17 ).…”
Section: Discussionmentioning
confidence: 67%
“…In one study, HIV-associated WM impairments in the DTI measure of mean diffusivity (MD) were found to be more severe in individuals with a history of substance abuse ( 19 ), providing preliminary evidence for a synergistic interaction of former substance abuse and HIV on WM pathology. However, another recent DTI study investigating the combined effect of current cocaine abuse and HIV on WM did not show a synergistic effect ( 20 ). In that study, Cordero and colleagues found no effect of current cocaine dependence on WM in both HIV+ and HIV− subjects ( 20 ), in contrast to a growing body of literature demonstrating WM impairment in current cocaine dependence ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation